Kazakhstan and the EU: from Cooperation Strategy to the New Agreement on the Advanced Partnership - R. S. Kurmanguzhin (Сравнительная политика)
The author presents key initiatives of the Republic of Kazakhstan to develop cooperation with the European Union – the largest economic, trade and investment partner of Kazakhstan – directed on achievement of level of partner cooperation with the EU and ensuring sustainable political and economic development of Kazakhstan.